2013
DOI: 10.1038/jhg.2012.158
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of previous genome-wide association studies with two distinct pathophysiological entities of gastric cancer in the Korean population

Abstract: Gastric cancer (GC) is the most common malignancy. The incidence rates remain remarkably high in East Asians. Although genome-wide association studies in the Han Chinese and Japanese populations have so far yielded susceptibility loci for GC, these findings need to be validated in an independent ethnic group. To identify the potential heterogeneity by histological classified subtypes (intestinal and diffuse), we examined the previously reported associations in the Korean population. PRKAA1 at 5p13.1 was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…A comparison based on histological type showed significant additive interactions only in intestinal‐type cancer; consistent with our results, Hwang et al. also indicated that the PRKAA1 SNP was more strongly associated with intestinal‐type gastric cancer than diffuse‐type gastric cancer . In addition, intestinal‐type gastric cancer is associated more with HP infection when compared to diffuse‐type gastric cancer , since stratified analysis for interaction between the PRKAA1 rs13361707 SNP and HP infection according to the anatomic location of cancer and histological type of cancer was considerably low.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A comparison based on histological type showed significant additive interactions only in intestinal‐type cancer; consistent with our results, Hwang et al. also indicated that the PRKAA1 SNP was more strongly associated with intestinal‐type gastric cancer than diffuse‐type gastric cancer . In addition, intestinal‐type gastric cancer is associated more with HP infection when compared to diffuse‐type gastric cancer , since stratified analysis for interaction between the PRKAA1 rs13361707 SNP and HP infection according to the anatomic location of cancer and histological type of cancer was considerably low.…”
Section: Discussionsupporting
confidence: 90%
“…Quality and quantity requirements for genotyping DNA samples were determined by identifying intact DNA bands after 2% agarose gel electrophoresis, and their concentrations were measured at >20 ng/ μ L with a degree of purity >1.7. Genotype analysis was performed for the five single‐nucleotide polymorphisms (SNPs; rs10074991, rs13361707, rs154268, rs3805486, and rs6882903) associated with PRKAA1 using a GoldenGate assay (Illumina, San Diego, CA, USA). The call rates for the examined samples and SNPs were 100%, with all five SNPs meeting the Hardy–Weinberg equilibrium in the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Shi et al 9 reported a genome-wide significant association for this SNP in a scan of non-cardia cancer and also tested the association using DNA samples from 905 cardia cancer patients. Other reports relating this SNP to gastric cancer from Korea have also confirmed an association, 12 with one study reporting that the association did not differ by location in the stomach. 13 Overall, there appears to be consistent evidence for an association with gastric non-cardia cancer, but the results for cardia are mixed.…”
Section: Discussionmentioning
confidence: 66%
“…Of them, two studies written in Chinese were excluded because of the overlap of study subjects [22, 32]. Moreover, one investigation was excluded for only focused on gastric survival not case-control study [51], three publications were excluded due to lack of genotyping data [52-54], one was not focused on cancer [55], and another two that did not pertain to either of these two polymorphism were also excluded [56, 57]. Eventually, 32 publications were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%